A review over the role of catalysts for selective short-chain polyglycerol production from biodiesel derived waste glycerol - Chong, C.C. (Elsevier B.V., 2020)
The production of biodiesel production has been surged throughout the decades due to the conventional transesterification process of edible, non-edible, and waste cooking oil to replace fossil-based fuels. Regrettably, this acclaimed process undeniably accompanied by glycerol generation as its primary by-product. The synchronous inclining trend of glycerol production with blooming biodiesel industries urged the wise utilization of market-surplus crude glycerol as well as to boost the market price of glycerol. One of the promising technologies for waste glycerol utilization is catalytic glycerol etherification for valuable polyglycerol (especially di- and triglycerol) production. Thus, the role of the catalysts during the reaction is noteworthy for the excellent glycerol conversion and short-chain polyglycerol yield. In this review, the homogeneous and heterogeneous catalysts reported in previous literature are reviewed and compared. The promising heterogeneous catalysts for glycerol etherification was divided into three main categories, viz. microporous, mesoporous, and macroporous. The recent wide application of cost-effective, highly stable, and environmentally benign natural clays as an alternative heterogeneous catalyst has also been included together with their modification treatments. Overall, this review provides appraisals on various catalysts used and challenges faced upon utilizing low-value surplus glycerol into valuable polyglycerol. Lastly, this review attempts to propose further investigations and explorations on more promising green catalysts as a substitution over commercial catalysts as one of the schemes for the future prospects of glycerol etherification. Â© 2020 Elsevier B.V.